175k views
0 votes
What is the first step in solving the equation 3.5 n + 6.4 = 42.5?

Add 6.4 to each side of the equation.
Subtract 6.4 from each side of the equation.
Multiply each side of the equation by 3.5.
Divide each side of the equation by 6.4.

User Davidriod
by
4.7k points

2 Answers

3 votes

Answer:

Subtract 6.4 from each side of the equation is your answer!

Explanation:

User Besthost
by
4.8k points
2 votes

Answer:

Subtract 6.4 from each side of the equation.

Explanation:

3.5 n + 6.4 = 42.5

-6.4 = -6.4

3.5 n = 36.1

3.5n/3.5n= 36.1/3.5n

n=10.3142857

Hope it helps!!!!

User Mazen K
by
4.8k points